Solitary fibrous tumor of the foramen of Monro. - Kinfe, Thomas M.; Tschan, Christoph A.; Stan, Alexandru C.; Krauss, Joachim K. (Clinical Neurology and Neurosurgery, 2008)
Solitary fibrous tumors have been described rarely in the central nervous system and only exceptionally within the ventricular system. This benign entity shows histoimmunochemically strong positivity for vimentin and calretinin. Little is known about the pathophysiological aspects. The authors report on a 75-year-old woman who presented with clinical signs of occlusive hydrocephalus including cognitive deficits, urine incontinence and gait disturbance. Imaging studies demonstrated a tumor at the foramen of Monro which was thought to be a colloid cyst and she underwent CSF shunting. After recurrent episodes of shunt dysfunction the tumor was removed via a transventricular approach guided by endoscopic ventriculoscopy. The histopathological examination revealed a solitary fibrous tumor. This is the first report on a solitary fibrous tumor located at the foramen of Monro in an elderly patient. Surgical removal has been considered to be the best therapeutic strategy in treating this rare entity with no need of postoperative adjuvant therapy. Further imaging and histological studies are needed to improve understanding of the pathophysiological aspects behind i
Keywords: Brain tumor; Solitary fibrous tumor; Third ventricle; Foramen of Monro